Biomarkers in aortic dissection: Diagnostic and prognostic value from clinical research - Yufei Zhao; Weiguo Fu; Lixin Wang; Ting Gao; Xiuyuan Hao (Chinese Medical Journal, 2024)
Abstract. Aortic dissection is a life-threatening condition for which diagnosis mainly relies on imaging examinations, while reliable biomarkers to detect or monitor are still under investigation. Recent advances in technologies provide an unprecedented opportunity to yield the identification of clinically valuable biomarkers, including proteins, ribonucleic acids (RNAs), and deoxyribonucleic acids (DNAs), for early detection of pathological changes in susceptible patients, rapid diagnosis at the bedside after onset, and a superior therapeutic regimen primarily within the concept of personalized and tailored endovascular therapy for aortic dissection.